Dampak Fitur Augmented Reality pada Aplikasi Mobile Shopping terhadap Keputusan Pembelian pada Generasi Z : Studi pada Konsumen First-Time Buyer - Ami Natuz Zahara; Dian Mahardi Lestari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the impact of implementing Augmented Reality (AR) features on mobile shopping applications on purchasing decisions of Generation Z consumers, especially first-time buyers. The research method uses a quantitative approach, the study involved 385 Generation Z respondents (aged 18-25 years) who were using AR features for shopping for the first time. The results of multiple linear regression analysis show that AR Visual Quality (X1), AR Interactivity (X2) and AR Ease of Use (X3) have a significant positive effect on Purchasing Decisions (p <0.000). The study revealed that 78.5% of AR features influence Generation Z in deciding to purchase on mobile shopping applications. In this case, it can be concluded that the presence of AR features can reduce Gen Z's hesitation in deciding to purchase for first-time buyers. Key factors influencing purchasing decisions include AR visualization quality, ease of use, and feature interactivity.